الإعلام التقليدي ودو ره في الحفاظ على المو ر وث المحلي في ظل البيئة الرقمية - زقاو شيماء; مفتاح نجاة; د/علال عبد القادر (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة: تناولت الدراسة موضوع "الإعلام التقليدي ودو ره في الحفاظ على الموروث المحلي في ظل البيئة الرقمية "إذ تهدف الدراسة إلى كشف مدى مساهمة الإعلام التقليدي المحلي ونقصد به الإذاعة المحلية لولاية الأغواط في التعريف وإبراز أهمية الموروث والثقافة الخاصة بها، لكون الإذاعة وسيلة إتصالية جماهيرية تخاطب كل طبقات المجتمع ولما لها من مميزات وخصائص تؤثر على المتلقي، لذا يمكن إدراجها في التعريف بالتراث المحلي ونقله ونشره. واعتمدت دراستنا على المنهج الوصفي لجمع المعلومات، أما عينة الدراسة فاخترنا عينة من طلبة قسم علوم الإعلام والإتصال وقد توصلنا من خلال الدراسة إلى مجموعة من النتائج أهمها: _ مساهمة الإعلام المحلي في الحفاظ على الموروث المحلي لولاية الأغواط _ تسعى إذاعة الأغواط في نقل كل ما يتعلق بالتراث _ مدى مساهمة البيئة الرقمية في تعزيز والحفاظ على مكانة الإذاعة _تساهم الإذاعة في بث أكبر عدد من البرامج الهادفة في إحياء التراث وترسيخه عبر الأجيال Abstract : The current study discusses "Traditional Media and its Role in Preserving Local Heritage in the Digital Age." The study aims to reveal the extent to which local traditional media, namely the Regional Radio of Laghouat Province, contributes in introducing and highlighting the importance of Laghouat’s heritage and culture, for the radio is a mass communication medium that addresses all society’s classes and because of its features and characteristics that affect the recipient. Hence, radio can be used for introducing, transmitting and spreading local heritage. This research study relies on the descriptive approach to collect data. As for the sample, a number of Media and Communication Sciences students have been selected. As a result of this study, we have reached the following significant conclusions :  Local media contributes to preserving local heritage in Laghouat.  Laghouat’s radio seeks to broadcast everything related to heritage of the region.  The extent to which digital broadcasting contributes to the promotion and preservation of the radio status.  The radio contributes to broadcasting the largest number of programs that aim at reviving the heritage and consolidating it for the next generations.
دراسة ميدانية على عينة من طلبة قسم الإعلام والاتصال - جامعة عمار ثليجي